Personality traits and gender: effects on self-efficacy at work - Robalino Guerra, Paulina Elizabeth (2019)
Introduction: Whereas personality traits represent stable individual characteristics that mostly derive from individual genetic endowment, self-efficacy can enhance learning and performance (Caprara et al. 2010). Self-efficacy is a crucial cognitive and motivational belief impacting on several aspects of behaviour at workplace. Self-efficacy has been related to the effort and perseverance, coping strategies to deal with labour demands, work engagement, and job performance. The aim of the present study was to analyse the effects and interaction effects of personality trails and gender on self-efficacy at work. Methodology: The participants were 314 employees from three different sectors (blue, white and pink collar), both gender (52.5% female), ages between 18 and 75 years old (M= 34.66; SD= 10.93). Factorial design 2 (low- high personality trail) x 2 (gender) was applied. We use a socio-demographic questionnaire; NEO-FFI Personality Inventory (Costa & McCrae, 1992) to measure Openness to Experience (á =.73), Agreeableness (á =.71), Emotional Stability (á =.82), Extroversion (á =.83) and Conscientiousness (á =.79); Self-efficacy at work scale (Loeb, et al, 2016, Spanish version Robalino & Musso, 2018) that measures self-efficacy for inter/intrapersonal processes, and occupational self-efficacy oriented to cognitive tasks in the workplace (á =.88).Results: Personality traits has a significant effect on self-efficacy. Specifically, Neuroticism on task self-efficacy (F(1,312)=50.168; p<.001; ç²=.139), Conscientiousness on task self-efficacy (F(1,312)=47.856; p<.001; ç²=.133), Extraversion on social self-efficacy (F(1,312)=45.440; p<.001; ç²=.127), Agreeableness on social self-efficacy (F(1,312)=33.321; p<.001; ç²=.096). In addition, Openness to Experience has an effect on self-efficacy in recognizing the emotions of others (F(1,312)=6.943; p<.01; ç²=.022). Moreover, there are significant gender differences in self-efficacy at work. Men have greater task self-efficacy (t(312)=-2.730; p<.01) and social self-efficacy (t(312)=-2.793; p<.0). There are no gender differences in self-orient emotional self-efficacy, emotional self-efficacy to understand-other, emotional self-efficacy to help others. Finally, MANOVA´s results suggest that there are no interactions effects between gender and personality traits on self-efficacy at work.